2002
DOI: 10.1002/j.0022-0337.2002.66.9.tb03577.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tobacco Counseling in the Dental Office

Abstract: This article describes the results of studies among dental care providers regarding tobacco cessation in the past two decades. In the early period, surveys described what dentists were doing in their own practices. The results suggested that they were not adequately communicating to their patients the importance of quitting. There is good evidence that brief interventions from health professionals can increase rates of smoking cessation. The outcome from a number of trials that examined the feasibility of cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 46 publications
5
84
1
4
Order By: Relevance
“…Other studies, including our own work, have shown that dentists and dental hygienists can be effective in helping their patients quit both smoking and using chewing tobacco [7,8,46,47]. In a review of six smoking cessation studies conducted in dental settings, Warnakulasuriya reported modest yet consistent increases in abstinence rates for interventions including behavioural and pharmacological treatments for tobacco dependence [8].…”
Section: Tobacco Cessation Interventions In Dental Settingsmentioning
confidence: 81%
See 1 more Smart Citation
“…Other studies, including our own work, have shown that dentists and dental hygienists can be effective in helping their patients quit both smoking and using chewing tobacco [7,8,46,47]. In a review of six smoking cessation studies conducted in dental settings, Warnakulasuriya reported modest yet consistent increases in abstinence rates for interventions including behavioural and pharmacological treatments for tobacco dependence [8].…”
Section: Tobacco Cessation Interventions In Dental Settingsmentioning
confidence: 81%
“…Tobacco plays a major role in the development and treatment of many oral diseases [1–4], and the repeated nature of dental treatment provides multiple opportunities for information, advice and brief counselling [5,6]. However, most dentists and dental hygienists in practice report lack of training in effective tobacco cessation skills as a significant barrier to incorporating these behaviours into routine care [7,8]. In this paper, we summarise the rationale for addressing tobacco use within dentistry and dental hygiene, review the extant policies regarding provision of tobacco‐related education, and make recommendations for the content and format of training in treatment of tobacco dependence in undergraduate and graduate curricula and continuing education courses.…”
Section: Introductionmentioning
confidence: 99%
“…Training programs for dentists and dental students have been implemented to include evidence‐based techniques in such areas as motivational interviewing, smoking cessation counseling, dental treatment of HIV+ patients and early detection of child abuse and neglect. These have been accompanied by documented changes in dentists’ confidence, behaviors and practices . Within the medical community, brief training for medical residents in the management of substance misuse has shown improvements in substance misuse inquiry, due notably to increased provider confidence and treatment optimism .…”
Section: Discussionmentioning
confidence: 99%
“…A brief motivational intervention during the dental visit has been reported to be more successful in motivating patients not intending to cease smoking than patients considering cessation within the next 6 months . Similar smoking cessation rates (10–15% per year) may be achieved for dental and general medical practices, in case the dental practice offers the patient structured cessation programmes . The odds of tobacco cessation are increased by interventions offered by oral health professionals .…”
Section: Smoking Cessationmentioning
confidence: 99%